Analisis Bentuk Keaktifan Belajar Siswa yang Dominan Muncul dalam Proses Pembelajaran Matematika di Sekolah Dasar - Muhaiminah Jalal; Fitri Kumala Dewi; Susan Diyani (Jurnal Ragam Pengabdian, 2026)
Based on observations conducted by researchers together with the fourth- grade homeroom teacher on Tuesday, August 10, 2025, at SDN 05/VIII Balai Rajo, problems were found related to student learning activity in mathematics learning. During the learning process, most students tended to be passive and did not show optimal involvement. Students mostly listened without responding, rarely asked questions, and were still limited in expressing opinions. This condition indicates that student learning activity is still relatively low. This study aims to describe in depth the dominant student learning activity that appears in the mathematics learning process. Data were collected through observation, interviews, and documentation, with research instruments that have been validated by expert validators. The results of the study indicate that the dominant forms of activeness that appear during mathematics learning include taking notes, paying attention to teacher explanations, participating in group discussions, and following up on teacher instructions quickly.